BROWSE SELECTION BY MOOSE IN THE ADIRONDACK PARK, NEW YORK - Peterson, Samuel; Kramer, David; Hurst, Jeremy; Frair, Jacqueline (Lakehead University, 2020)
Moose (Alces alces americana), a large-bodied and cold-adapted forest herbivore, may be vulnerable to environmental change especially along their southern range in the northeastern United States. Better understanding of moose foraging patterns and resource constraints in this region, which moose recolonized over the past several decades, is needed to anticipate factors that may influence the long-term viability of the regional moose population. We quantified browse selection, intensity and nutritional quality, and the impact of other vegetation potentially interfering with browse availability for moose within the Adirondack Park, New York. We backtracked GPS-collared female moose (n = 23) to assess the seasonal composition of selected browse from 2016 to 2017, compared browse selection to plant nutritional quality, and modeled local browsing intensity. Moose demonstrated a generalist feeding strategy in summer, but in winter selected browse species largely in order of digestible dry matter. Red maple (Acer rubrum) was the most heavily used species in both seasons. Areas having a high proportion of beech (Fagus grandifolia), which in this region regenerates in dense thickets in the aftermath of beech bark disease and thwarts timber regeneration, were associated with reduced browsing intensity by moose in both seasons. Given the limited amount of timber harvest within the Adirondack Park, thoughtful management of harvested stands may increase marketable timber while also benefitting moose and ensuring the longevity of the New York population.